Multicentre study of neoadjuvant chemotherapy for stage I and II oesophageal cancer. Issue 7 (4th April 2016) - Bekkar, S.; Gronnier, C.; Renaud, F.; Duhamel, A.; Pasquer, A.; Théreaux, J.; Gagnière, J.; Meunier, B.; Collet, D.; Mariette, C.; ,
Abstract : Background: The benefit of neoadjuvant chemotherapy (NCT) for early‐stage oesophageal cancer is unknown. The aim of this study was to assess whether NCT improves the outcome of patients with stage I or II disease. Methods: Data were collected from 30 European centres from 2000 to 2010. Patients who received NCT for stage I or II oesophageal cancer were compared with patients who underwent primary surgery with regard to postoperative morbidity, mortality, and overall and disease‐free survival. Propensity score matching was used to adjust for differences in baseline characteristics. Results: Of 1173 patients recruited (181 NCT, 992 primary surgery), 651 (55·5 per cent) had clinical stage I disease and 522 (44·5 per cent) had stage II disease. Comparisons of the NCT and primary surgery groups in the matched population (181 patients in each group) revealed in‐hospital mortality rates of 4·4 and 5·5 per cent respectively ( P = 0·660), R0 resection rates of 91·7 and 86·7 per cent ( P = 0·338), 5‐year overall survival rates of 47·7 and 38·6 per cent (hazard ratio (HR) 0·68, 95 per cent c.i. 0·49 to 0·93; P = 0·016), and 5‐year disease‐free survival rates of 44·9 and 36·1 per cent (HR 0·68, 0·50 to 0·93; P = 0·017). Conclusion: NCT was associated with better overall and disease‐free survival in patients with stage I or II oesophageal cancer, without increasing postoperative morbidity. Abstract : Improves survival